Carnivalesque collaborations: reflections on 'doing' multi-disciplinary research. (October 2015) - Spiller, Keith; Ball, Kirstie; Daniel, Elizabeth; Dibb, Sally; Meadows, Maureen; Canhoto, Ana
Many funding bodies emphasize the advantages of using multi-disciplinary approaches; in response, in this article we consider our reflections on doing such a project. We contribute to the multi-disciplinary literature by considering the standardizing effect of collaboration on multifarious research approaches. We argue that greater attention should be paid to 'doing' qualitative multi-disciplinary research. We find that elements of 'letting go' and 'coming together' are important when new perspectives and knowledge are engaged. Therefore, we call for clarity on the multi-disciplinary approaches and discuss how we came to understand the collaborative processes of researching, thinking, and writing. The paper begins with vignettes about our ontological journeys during the research project. In developing our argument, we consider the retrospective and reflexive qualities expressed in our vignettes and examine how our collaborative theorizing shaped the research project.